Reduced Sense of Coherence Due to Neuroticism: Are Transcendent Beliefs Protective Among Catholic Pastoral Workers? - Kerksieck, Philipp (Journal of religion and health, 2017)
In this study, we examined a third variable effect on the relationship of personality traits, especially neuroticism and the salutogenetic concept sense of coherence. Specifically, we were interested in the moderating role of religious trust (RT) and transcendence perception operationalized as daily spiritual experiences (DSE) on the aforementioned relationship among religious individuals. We applied a cross-sectional study among a sample of 8594 pastoral workers using standardized questionnaires. Multiple regression and moderator analysis displayed the relationships between big five personality variables and sense of coherence. Neuroticism was identified as a negative predictor to sense of coherence, indicating impairment on this psychological resource. RT and DSE appear to function as moderators that buffer the negative effects of neuroticism on sense of coherence among religious persons. This is an interesting finding because people with expressions of neurotic personality tendencies often struggle to find helpful methods of coping and may find a helpful resource in the concepts studied here.